EFL LEARNERS ATTITUDE TOWARDS PODCASTS FOR EXTENSIVE LISTENING - Angelia, Christela; Juliaty, Hanna (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
One of online materials used more frequently nowadays in Extensive Listening (EL) is podcasts. Similar with other learning materials, podcasts are classified into authentic podcast and language course (non-authentic) podcast. Previous studies have examined learners attitude towards podcasts; yet, they generally regarded all podcasts as authentic material. In EL, learners attitude towards the materials also affects the success of EL. Therefore, this study aimed to examine EFL learners attitude towards authentic podcast and language course podcast in EL. The study was conducted in a qualitative within-subject design and involved six English Department students from a private university in Indonesia. The students took part in an EL program using both authentic and language course podcasts, shared their experience in learning journals, and participated in post-activity interviews. The data collected were analyzed qualitatively using Ajzens (2005) classification of attitude elements. The findings showed that despite the favorable attitude that the learners mostly displayed towards both types of podcasts, there was a significant difference in the cognitive, affective, and conative aspects of their attitude that influenced their overall attitude. The findings implied that both types of podcasts have potentials to be used for EL by EFL learners with some considerations.